Minimum Wages and the Labor Market Effects of Immigration - Anthony Edo; Hillel Rapoport (Institute of Labor Economics (IZA), 2018)
This paper exploits the non-linearity in the level of minimum wages across U.S. States created by the coexistence of federal and state regulations to investigate the labor market effects of immigration. We find that the impact of immigration on the wages and employment of native workers within a given state-skill cell is more negative in States with low minimum wages and for workers with low education and experience. That is, the minimum wage tends to protect native workers from competition induced by low-skill immigration. The results are robust to instrumenting immigration and state effective minimum wages, and to implementing a difference-in-differences approach comparing States where effective minimum wages are fully determined by the federal minimum wage to States where this is never the case.
Keywords: F22; J61; 330; immigration; minimum wages; labor markets